Unsaturated copolyesters of lactide. Issue 96 (30th September 2016) - Lahcini, M.; Weidner, S. M.; Oumayama, J.; Scheliga, F.; Kricheldorf, H. R.
Abstract : Four classes of unsaturated copolyesters of l -lactide were prepared either from isosorbide or bis(hydroxymethyl)tricyclodecane in combination with fumaric acid or from 1, 4-butenediol or 1, 4-butynediol with terephthalic acid. Abstract : Four classes of unsaturated copolyesters of l -lactide were prepared either from isosorbide or bis(hydroxymethyl)tricyclodecane in combination with fumaric acid or from 1, 4-butenediol or 1, 4-butynediol with terephthalic acid. All syntheses were performed in such a way that lactide was oligomerized with a diol as the initiator and the resulting oligomers were polycondensed with a dicarboxylic acid dichloride either in a one-pot synthesis or in a two-step procedure. For most copolyesters the SEC measurements gave weight average molecular weights in the range of 30–60 kg mol −1 and dispersities in the range of 4.2–6.2. The MALDI-TOF mass spectra displayed a high content of cycles and indicated an irreversible kinetic course of all polycondensations. Glass-transition temperatures ( T g ) above 90 °C were only found for two copolyesters of isosorbide. Addition of bromine to copolyesters of 1, 4-butenediol yielded flame retarding biodegradable polymers.